(untitled) (Journal of Hama University, 2025)
Anaerobic digestion is a promising option for environmentally friendly recycling of agricultural by-products and renewable resources energy production. The aim of this research is study the influence of co-fermentation of broad beans wastes (BW) with cow manure (CM) on Biogas production. (ratios of BW to CM are 75:25,50:50,25:75) Eudiometer batch digesters of one litre capacity were used and the temperature was set at 37 C°. Hydraulic retention time was 30 days. Biogas and methane yields ranged from 147-262 and 82-144 LN/Kg VS. the methane content of the biogas was of 55-58%, the remaining being principally CO2. The co-digestion ratio between BW and CM which gave the maximum biogas and methane yield (191 LN/Kg VS - 109 LN/Kg VS) respectively, was observed to be 50:50. The ratio which gave high concentration of methane in the biogas (58%) was observed to be 75:25. The necessary digester retention time recommended to achieve high rate biodegradation is between 11 and 21 days for BW, CM and their mixtures.